Clematis serrana (Ranunculaceae), a new endemic species to the Atlantic Forest highlands in Southern Brazil - Piovesani, Willian Souza; Ferreira, Priscila Porto Alegre; Seger, Guilherme Dubal Dos Santos (Phytotaxa, 2024)
A new species of Clematis (Ranunculaceae) from the Southern Brazilian Plateau is described here. The species shares similarities with C. denticulata and C. ulbrichiana, but can be distinguished mainly by the staminate partial inflorescences in compressed cymes (false whorls), pyriform staminate flower buds, and fewer carpels. Along with the description, we provide a preliminary extinction risk assessment and photographic plates for the new species. Identification keys for the species in the Atlantic Forest Biome are also presented.